GP91 Screening for cystic fibrosis related liver disease with ultrasonography. (June 2019) - Cooney, Hannah; Shanthikumar, Shivanthan; Robinson, Philip
Abstract : Introduction: Respiratory manifestations of cystic fibrosis (CF) have historically been the factor limiting prognosis. As there have been improvements in management of respiratory issues, increased screening and management of other manifestations of CF is required. CF related Liver Disease (CFLD) usually presents before or during adolescence and 5–10% of patients develop clinically significant disease. Diagnosis of CFLD is defined by two of the following; abnormal clinical examination, persistent liver function test (LFT) derangement or ultrasonographic evidence of disease. Available clinical guidelines for infants with CF recommend screening for CFLD. The Royal Brompton Care of Children with CF guideline and the CF Trust Standards of Care suggest routine abdominal ultrasound (US) screening from age 5. In contrast, the NICE guidelines do not specify an age at which to commence screening. Given the high treatment burden for patients with CF, we examined whether routine abdominal ultrasound screening for CFLD at age 5 leads to intervention or changes in clinical management. Method: We conducted a retrospective analysis of routine abdominal US screening conducted in CF patients at age 5, at the Royal Children's Hospital (Melbourne, Australia). The primary outcome measure was whether the US results led to a clinical intervention defined as treatment with ursodeoxycholic acid. Additional data collected included patient demographics, pancreatic and nutritional status, LFT result (normal, clinically insignificant, or clinically significant based on Royal Brompton Care of Children with CF guideline), referral to a hepatologist and timing of next US. Results: Between 2012 and 2017, 31 CF patients had a US at age 5 years. 22 patients (71.0%) had no sonographic evidence of CFLD at time of first screening US. The remaining 9 patients (29.0%) displayed only mild evidence of CFLD. One patient (3.1%) was commenced on ursodeoxycholic acid. Two patients (6.2%) were referred to a hepatolgoist. Follow up US was conducted an average of approximately 2 years following initial US. Mild clinically insignificant LFT derangement was common (74.1%) but, all patients who had completely normal LFT results had no US evidence of disease. Conclusions: These results suggest that US conducted at age 5 rarely alters clinical management. Although US is a non-invasive investigation, CF patients already have a high treatment burden and given US at 5 years is highly unlikely to change management, it is unnecessary (especially in those with normal LFT's). Further investigation is needed to determine the optimal age to commence US screening for CFLD.